2019
DOI: 10.24926/iip.v10i4.2237
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Advanced Practice Pharmacist Type 2 Diabetes Management Program: A Pilot Study

Abstract: Background: The purpose of this study was to describe the impact of an Advanced Practice Pharmacist (APh) on lowering hemoglobin A1c (HbA1c) in patients with type 2 diabetes within a patient centered medical home (PCMH) and to classify the types of therapeutic decisions made by the APh. Methods: This was a retrospective study using data from electronic health records. The study evaluated a partnership between Chapman University School of Pharmacy and Providence St. Joseph Heritage Healthcare that provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“… 34 Similarly, Lewis and colleagues (2019) demonstrated that APhs significantly lowered hemoglobin A1c in patients with diabetes mellitus. 35 Neither study included a comparison group of non-APhs, limiting the ability to evaluate the outcomes of APhs relative to other pharmacists providing similar clinical services. In addition, other prior studies demonstrate that pharmacists without APh credentials have also had success in managing diabetes and anticoagulation clinics, thus it is not possible to conclude that the APh alone was responsible for the clinical outcomes achieved.…”
Section: Implementation Of the Advanced Practice Pharmacist (Aph) Des...mentioning
confidence: 99%
“… 34 Similarly, Lewis and colleagues (2019) demonstrated that APhs significantly lowered hemoglobin A1c in patients with diabetes mellitus. 35 Neither study included a comparison group of non-APhs, limiting the ability to evaluate the outcomes of APhs relative to other pharmacists providing similar clinical services. In addition, other prior studies demonstrate that pharmacists without APh credentials have also had success in managing diabetes and anticoagulation clinics, thus it is not possible to conclude that the APh alone was responsible for the clinical outcomes achieved.…”
Section: Implementation Of the Advanced Practice Pharmacist (Aph) Des...mentioning
confidence: 99%
“…Embedded pharmacists may be physically located onsite five days a week or less often, depending on the size of the primary care office and the other responsibilities of the pharmacist in providing care via other disease management clinics or teaching requirements for those with faculty appointments at a college of pharmacy. 24,25 It is now common for embedded pharmacists to manage patients with diabetes through independent prescribing based on CDTM agreements, however there are other successful patient care models that have been described. These models include joint pharmacist-physician appointments in which both professionals evaluate the patient and develop a treatment plan at the point of care, pharmacist-patient appointments in which the pharmacist discusses each patient with the PCP to develop a treatment plan at the point of care, or pharmacist appointments where recommendations are provided via the EHR (electronic health record) to the PCP for implementation by the PCP or for implementation by the pharmacist following PCP authorization.…”
Section: Pharmacists In Primary Carementioning
confidence: 99%
“…Thus, pharmacist-managed diabetes programs that include management of hypertension, hyperlipidemia, and nicotine cessation are commonly found within primary care settings. 24,26,30 Given the unique barriers that many PCPs face in caring for patients with diabetes along with the growing shortage of available PCPs, primary care is an ideal environment for pharmacists to assist with care delivery.…”
Section: Dovepressmentioning
confidence: 99%
“…Pharmacists have been involved in chronic disease management, taking direct responsibility for patients’ disease states, medications and overall management to improve outcomes 24 25. Extensive global studies have demonstrated the effectiveness of pharmacist-based interventions on patients with diabetes, resulting in improved quality of care and clinical outcomes 23 26 28–30. In addition, several systematic reviews31–34 have identified various non-pharmacological pharmacist-led interventions, such as diabetes education,35–38 medication review,39 drug counselling/advice,40 41 lifestyle modification, self-care, peer support and behavioural intervention 42–44…”
Section: Introductionmentioning
confidence: 99%